2007
DOI: 10.1111/j.1468-0335.2006.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Wage Subsidies Increase Employment in Subsidized Firms?

Abstract: This paper examines whether subsidized jobs have contributed to employment in subsidized firms or have merely substituted for non-subsidized ones. The data-set is an unbalanced panel of some 31,000 firms that are followed annually between 1995 and 2002. The analysis is based on difference-in-differences, which is adjusted by regression and matching methods. The results indicate that wage subsidies stimulate employment, and that the magnitude of the effect is as aimed. I also found that subsidies have no sizeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
36
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 28 publications
5
36
0
2
Order By: Relevance
“…209 Similar results are found by Kangasharju and Venetoklis (2003) and Hietala and Hietala (2004): the latter study found that the Combined Subsidy had almost negligible displacement effects.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…209 Similar results are found by Kangasharju and Venetoklis (2003) and Hietala and Hietala (2004): the latter study found that the Combined Subsidy had almost negligible displacement effects.…”
supporting
confidence: 69%
“…Kangasharju (2007) examines whether subsidised jobs, which have contributed to employment in subsidised firms, have merely substituted for non-subsidised ones. The results indicate that wage subsidies stimulate total employment, and have no sizeable effects on non-subsidised firms in the industry or the geographical area in question.…”
mentioning
confidence: 99%
“…In general, wage subsidies are aimed at compensating the disadvantage position and (thereby) the potentially (perceived) lower productivity of the targeted workers. In that respect, wage subsidies for the disabled are quite comparable to subsidies targeted at other groups, as theoretically and empirically evaluated by, e.g., Bell et al [5], Burtless [8], Gerfin et al [16], Jaenichen and Stephan [20] and Kangasharju [21]. subsidy of one-third to two-thirds of the wage they pay to disabled workers.…”
Section: Introductionmentioning
confidence: 77%
“…See e.g. Mühlau and Salverda, 2000 for the Netherlands, and the references for Finland cited in Kangasharju (2007), although Kangasharju himself finds more sizable employment effects.…”
mentioning
confidence: 99%
“…While these broad measures reduce labour costs for all workers in a particular wage range, many countries operate wage subsidies targeted at specific types of workers such as young or older workers (see OECD series Jobs for Youth and Ageing and Employment Policies), individuals with disabilities or healthrelated problems (see OECD series Sickness, Disability and Work), or the long-term unemployed (e.g., Kangasharju, 2007;Bernhard et al, 2008). They may be available permanently (for as long as the employment relationship lasts), or for limited periods of time.…”
mentioning
confidence: 99%